2018
DOI: 10.1002/rth2.12112
|View full text |Cite
|
Sign up to set email alerts
|

Imaging platelet biogenesis in vivo

Abstract: In this review paper, we give a historical perspective of the development of imaging modalities to visualize platelet biogenesis and how this contributed to our current understanding of megakaryopoiesis and thrombopoiesis. We provide some insight how distinct in vivo and in situ imaging methods, including ultramicrographs, have contributed to the current concepts of platelet formation. The onset of intravital microscopy into the mouse bone marrow has markedly modified and challenged our thinking of platelet bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The recent development of new bone cutting and staining methods [25], the availability of more subtype-specific antibodies, together with novel microscopic approaches that allow the acquisition of overview images of whole bones by maintaining high resolution images for detail analyses, has enabled the in-depth analysis of MK matrix interactions in situ. These advancements now allow to deduce an organ-wide information on biological processes [26].…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of new bone cutting and staining methods [25], the availability of more subtype-specific antibodies, together with novel microscopic approaches that allow the acquisition of overview images of whole bones by maintaining high resolution images for detail analyses, has enabled the in-depth analysis of MK matrix interactions in situ. These advancements now allow to deduce an organ-wide information on biological processes [26].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, platelet spreading assays, which are not affected by low platelet count, can help define bleeding phenotypes in patient samples that are negative for an aggregation defect (85). The combination of biological optical microimaging with genomic information has opened up new avenues to test and evaluate these rare conditions that are not limited by low platelet counts but are still constrained by the limits of optical diffraction (86,87).…”
Section: Micro-imaging Platelets In a Dishmentioning
confidence: 99%
“…Studies using transgenic mice expressing LifeAct-GFP have also revealed details of platelet actin cytoskeletal structure and nodules (65, 163). When pairing these fluorescent transgenic mice with an intravital microscope, it becomes possible to delve deep underneath dense tissue and potentially observe megakaryopoiesis and changes in ploidy and proplatelet formation and release into the blood stream (87,164). Fluorescently-labeled platelets have enabled studies of platelet migration and platelet interactions with other blood cells, in a number of physiology scenarios, including inflammation (139), infection (165), and cancer (166).…”
Section: Hemostasis and Thrombus Formation In Its Natural Microenviromentioning
confidence: 99%
“…Thus, at present, it is completely unknown if platelets can escape from the ridge area in the same manner as RBCs. Since it is extremely difficult to image platelets under visible or near-infrared light without labeling, fluorescence imaging has typically been employed for this purpose [34][35][36]. However, the rate of blood flow inside the hydrodynamic bearing of a rotary blood pump is very high, so it will be necessary to development a process allowing the high-speed fluorescent imaging of platelets.…”
Section: Limitations and Future Workmentioning
confidence: 99%